Integrating Poultry into a Crop and Pasture Farming System - Glatz, P.C.; Ru, Y.J.; Miao, Z.H.; Wyatt, S.K.; Rodda, B.J. (International Journal of Poultry Science, 2005)
Small scale operations in which poultry forage freely around farms is widespread on rural properties. In Australia grain farmers, market gardeners and graziers integrate poultry into their farming system. In this system, birds are unrestricted in their movements except that they are usually locked in sheds at night for protection from predators. Consumers pay a premium for eggs and chicken meat on the grounds of enhanced welfare of birds in this system. Eggs are perceived as having superior taste and nutritional properties. The purpose of this experiment was to determine the impact of poultry integrated into a pasture and crop rotation system. The pasture availability, insects, weeds and soil fertility were measured before and after grazing by poultry. Sheep were used as a comparison in the experiment. Laying hens stocked at 110/ha (compared to sheep-stocking density 12/ha) were allowed to forage a medic pasture in a crop and pasture rotation system during summer in a Mediterranean environment. The egg production of layers (Hyline Brown) in the free-range system was lower than the standard performance expected in a cage system. Rate of lay from 18-40 weeks was 79% vs 93% (cage standard). The mortality of free-range birds was higher than the cage standard (9.1 vs 1.2%). The reduction of performance of birds relative to the standard was expected considering the heat wave conditions experienced during the experiment. Sheep were very effective in grazing the wire seed, which contaminated the paddocks whereas poultry avoided this weed. In contrast, the number of unidentified weeds in the sheep paddocks was greater than the poultry paddock. This raises the possibility that sheep and poultry could be grazed together in some circumstances, to provide a method for reducing weed build up. Sheep could be used to graze out weeds they prefer and poultry to consume weed seeds and insects that sheep avoid. Soil fertility was not different between the sheep and poultry paddocks. The yield of wheat from poultry paddocks in the subsequent crop was 1.25 tonne/ha versus 1.43 tonnes/ha from sheep paddocks.